If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(3x^2-5x+1)=(x2+4x+2)
We move all terms to the left:
(3x^2-5x+1)-((x2+4x+2))=0
We add all the numbers together, and all the variables
-((+x^2+4x+2))+(3x^2-5x+1)=0
We get rid of parentheses
-((+x^2+4x+2))+3x^2-5x+1=0
We calculate terms in parentheses: -((+x^2+4x+2)), so:We add all the numbers together, and all the variables
(+x^2+4x+2)
We get rid of parentheses
x^2+4x+2
Back to the equation:
-(x^2+4x+2)
3x^2-5x-(x^2+4x+2)+1=0
We get rid of parentheses
3x^2-x^2-5x-4x-2+1=0
We add all the numbers together, and all the variables
2x^2-9x-1=0
a = 2; b = -9; c = -1;
Δ = b2-4ac
Δ = -92-4·2·(-1)
Δ = 89
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-9)-\sqrt{89}}{2*2}=\frac{9-\sqrt{89}}{4} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-9)+\sqrt{89}}{2*2}=\frac{9+\sqrt{89}}{4} $
| 25c2-12=1 | | 24-5-10a=-3(4-7a | | 9y–5=22 | | 8x+8x1=-1 | | x-(52-x)=20 | | 15c=90;c=6 | | -1(-2x+1)=9-14x | | 6x-65=3x+13 | | 3(4n+2)=-2(4n+6) | | -9x+30=-5(x+2) | | (8x+9)=(11x+12) | | 2(6x-3)=7(7x-1.2) | | 115+(x+27)=180 | | (4v-3)(v-5=) | | –8s+7=–7s | | 26=6k | | 7(x+5)=24 | | |5m+9|=-31 | | -4r+8+5=-15-3r | | 5w+8.6=-3.4 | | 8(x+5.75)=16(3x+1.50) | | 3/5(x-19)=5 | | 9-2(x+7)=21 | | 22+54x=+60x | | 120=6r | | 5y+6=4y+12 | | 16.95+(.5n)=22.95+(.2n) | | 24m-12=-84 | | 70=3g | | u-2.89=9.3 | | 90=6x-2+20 | | 24=12a-6 |